Exploring Generational Differences in Attitudes towards SOPs during Covid-19: A Smart Lockdown Case Study - Alvi, Mobashira; Ehsan, Nadeem (Pakistan Journal of Humanities and Social Sciences, 2023)
In Pakistan, government efforts to stem the spread of COVID-19 met with resistance due to the country's preexisting social, political, economic, and cultural conditions. The preceding pandemic shows that generational attitudes, social norms, and cultural practices can hinder the control of COVID-19. Therefore, the purpose of this study was to investigate the generational knowledge of COVID-19 and its openness to preventative measures to better comprehend the generational differences that exist with regard to the COVID-19 pandemic. Purposive sampling was used in our qualitative exploratory research in twin cities of Pakistan, i.e., Rawalpindi and Islamabad. To learn how Pakistani generations X, Y, and Z feel about and deal with COVID-19, we conducted in-depth interviews with members of these groups. This included both young and elderly persons of both genders. Manual content analysis was used to examine the data of the present study. The purpose of this study was to investigate the generational knowledge of COVID-19 and its openness to preventative measures to better comprehend the generational differences that exist with regard to the COVID-19 pandemic. Purposive sampling was used in our qualitative exploratory research in twin cities of Pakistan, i.e., Rawalpindi and Islamabad. A total of six in-depth, face-to-face interviews were conducted and a total of six major themes emerged: (1) generational differences in knowledge and perceptions of COVID-19; (2) trusted and preferred sources of health information; (3) different generations’ reactions to the first reports of the COVID-19 pandemic; (4) generational practices to prevent exposure from COVID-19; (5) different generational beliefs about the risks of not adhering to infection control procedures; and (6) generational willingness to prevent future outbreaks. The findings of the data showed that among all generations, younger people of Generation Z, in particular, tended to disregard safety rules because they were anxious to meet their friends and go back to normal. Overall, all generations showed a positive attitude towards smart lockdown and following SOPs to help prevent themselves and their loved ones from this disease. The findings of the present study provide an early indication of how different generations feel about the pandemic threat posed by COVID-19. Besides, the goal of this study was to inform the development of national policy for coronavirus pandemic containment strategies. Knowing how people feel about the pandemic and containment measures, in particular, would help policymakers devise measures that are more likely to be followed, so slowing the spread of the virus.